RANCANG BANGUN TEMPAT SAMPAH OTOMATIS BERBASIS MIKROKONTROLER ARDUINO UNO DENGAN SENSOR HC-SR04 - Roihatur Rohmah; Putri Lian (Jusikom : Jurnal Sistem Komputer Musirawas, 2022)
Waste is the most common problem in everyday life. Waste that is scattered and piled up can become a hotbed of disease, especially during the current Covid-19 pandemic. In this study purpose to design and build a trash can works automatically. The method in design and build an automatic trash can is using waterfall method. The trash can designed using Arduino Uno microcontroller, HC-SR04 sensor and SG90 servo motor. The automatic trash can works is to detect the distance then processed by the arduino microcontroller and so SG90 servo motor will move to open and close the trash can automatically. The result of this research is that the design of the trash can can be opened with an object distance of less than 50 cm and will close for pause of 5 seconds.